Variation of the 4 × 1 to 8 × 2 structural transition temperature of quasi-one-dimensional indium chains upon carrier doping from Si(111) substrates. (15th July 2020) - Ogino, Takahiro; Kuzumo, Valentin Motoi; Yamazaki, Shiro; Nakatsuji, Kan; Hirayama, Hiroyuki
Abstract: We investigated the 4 × 1 to 8 × 2 structural transition temperature of quasi-one-dimensional indium chains on the (111) surface of Si substrates possessing various carrier concentrations via low-energy electron diffraction. The transition temperature was found to decrease from 120 K to below 77 K with increasing carrier concentration on both n- and p-type Si(111) substrates. This decrease in the transition temperature was found to be proportional to the shift of the Fermi level, which was numerically evaluated using a one-dimensional charge transfer model of the interface. The obtained results demonstrate that doping of the surface state with both electrons and holes can be readily controlled by judicious selection of Si substrates with appropriate carrier type and concentration.